The role of family communication in the cognitive development and psychosocial adjustment of adolescents: the impact on the formation of self-concept - Sigüenza Campoverde, Wilson Guillermo; Chamba Leiva, Katy Maricela; Andrade Mejía, Diego Segundo; Moreno Yaguana, Paulina Elizabeth; Vilchez Tornero , Jose Luis (Transformación, 2024)
Objetive: Scientific literature argues the influence of family communication on the development of cognitive functions and the consequent psychosocial adjustment of adolescents; in turn, it relates to the formation of their self-concept. This paper aims at exploring the perception of family communication impact into the autoconcept education, focusing family communication from the perspective of adolescents. Methods: The authors follow a quantitative correlational-cross-sectional design in a sample of 317 participants (ages between 14 and 17 years) from the city of Loja, Ecuador. To measure the variables, the Parent-Adolescent Communication Scale (PACS) and the Self-Concept Questionnaire Form 5 (AF-5) were used. Results: The findings reveal that communication, in terms of degree of openness (PACS), shows significant direct correlations with the academic, social, emotional, family and physical self-concept. On the other hand, the magnitude of problems dimension (PACS) is indirectly associated with the emotional and family self-concept. These results emphasize the importance of encouraging open and healthy communication in the family environment as a means to promote a healthy self-concept. Conclusions: Family environment should include affective, assertive participating mechanism to create confidence and favoring the adolescent formation of self-concept.